Predictors of Financial Management Behavior of Public Secondary School Teachers in a Municipality of Davao de Oro - Remis, Radny Collin L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Poor financial management, which results in financial problems, affects one’s productivity in the workplace; thus, an individual cannot perform competently once preoccupied with financial distress. This study aimed to investigate whether financial knowledge, financial attitude, and locus of control significantly predict the financial management behavior of the public secondary school teachers in a municipality of Davao de Oro, Philippines. The researcher used the descriptive-correlational research design. The respondents were 192 purposively chosen secondary school teachers in the East and West districts in the municipality of Davao de Oro for the school year 2021-2022. Sets of adapted survey questionnaires were used in this study. Data were analyzed using descriptive and inferential statistics such as Pearson’s r and regression analysis. Findings reveal that financial knowledge was evident, financial attitude and financial management behavior were favorable, while the locus of control was manifested. Moreover, financial knowledge, financial attitude, and locus of control were significantly correlated with financial management behavior. However, only financial knowledge and locus of control could significantly predict financial management behavior in its individual capacity. Thirty-five percent of the variation in financial management behavior could be attributed to the combined influence of these factors.